2019
DOI: 10.14393/bj-v35n1a2019-42250
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria, typhoid and co-infection in District DIR (lower), Pakistan

Abstract: Malaria and typhoid fever are among the most endemic diseases in the tropical and developing countries. Both diseases share similar transmission factor and often have the similar symptom. Based on this reason, much medical personnel try to cure both malaria and typhoid instantaneously in each case of suspected Salmonella infection and vice versa. The District Dir (Lower) is a favorable location for the protozoan nourishment and secondly mostly reported cases of malaria and typhoid co-infections. The main objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
3
6
1
Order By: Relevance
“…The present study found 4.7% prevalence of typhoid and malaria coinfection, and a similar low prevalence of 4% was reported in Dhir District of Pakistan [24]. 3.9% prevalence was reported by Afoakwah et al [25] in Ghana.…”
Section: Age-wise Prevalence (%)supporting
confidence: 90%
“…The present study found 4.7% prevalence of typhoid and malaria coinfection, and a similar low prevalence of 4% was reported in Dhir District of Pakistan [24]. 3.9% prevalence was reported by Afoakwah et al [25] in Ghana.…”
Section: Age-wise Prevalence (%)supporting
confidence: 90%
“…Malaria and TF, whose clinical sign dominating is the fever, are due to two distinct pathogens, with different transmission modes. In fact, human malaria is caused by 5 haematozoa parasite species, Plasmodium genus and transmitted actively by Anopheles female mosquito infecting bite [7]. Salmonella TF is due to invasive enteric bacteria, Salmonella genus and transmitted through the oral route consuming water and food contaminated by infected faeces [8].…”
Section: Introductionmentioning
confidence: 99%
“…Co-infections with malaria and typhoidal/NTS were reported in 4,523 cases from 73,775 total patients enrolled in the 81 included studies. Co-infections with malaria and typhoidal Salmonella spp., including S. typhi and S. paratyphi , were reported in 3813 cases from 56 studies 31 , 36 , 38 , 39 , 41 43 , 45 – 48 , 50 – 52 , 57 , 59 , 61 , 65 68 , 70 , 71 , 73 78 , 81 84 , 86 108 . Co-infections with malaria and NTS, such as S. typhimurium , were reported in 707 cases from 18 studies 17 , 27 31 , 44 , 53 , 56 , 60 , 62 , 69 , 72 , 79 , 80 , 84 , 85 , 93 .…”
Section: Resultsmentioning
confidence: 99%
“…For the identification of malaria, Plasmodium spp. infections were identified via microscopy alone (52/81, 64.2%) 17 , 27 , 28 , 30 , 31 , 36 38 , 40 , 43 , 45 47 , 50 – 53 , 56 , 59 , 60 , 63 65 , 68 , 72 , 75 , 77 , 79 87 , 89 , 90 , 92 – 100 , 102 , 105 – 108 , microscopy/RDT (16/81, 19.8%) 20 , 41 , 44 , 49 , 54 , 58 , 61 , 66 , 69 , 71 , 74 , 78 , 88 , 91 , 103 , 104 , RDT alone (5/81, 6.17%) 57 , 67 , 73 , 76 , 101 , molecular method 39 , 55 , microscopy/RDT/molecular method 35 , 69 , not specified 42 , 48 , 70 , and ELISA 29 .…”
Section: Resultsmentioning
confidence: 99%